Self-Sustaining Solar Panel Cleaning Solution with Integrated IoT Monitoring - Yusoff Zaki, Ahmad Baihaqie; Abdullah, Mohammad Faiz Liew (Journal of Electronic Voltage and Application, 2025)
Deposition of dust on photovoltaic panels significantly reduces their power output efficiency, posing a major hindrance to optimal solar energy generation. In this article, the development of a self-sustaining solar panel cleaning system with an inbuilt Internet of Things (IoT) platform for real-time monitoring and control is reported. The system design suggested herein combines a wiper mechanism and a centrifugal air blower powered by a monocrystalline solar panel for effective removal of dust and debris. The cleaning cycle is made automatic using a dust sensor and real-time clock (RTC) module with an override facility through the Blynk IoT interface. Environmental and electrical parameters such as dust density, panel output voltage, current, and power are also monitored by the system. Results indicated a considerable power output increase after cleaning operations, validating the effectiveness and feasibility of the system as a cost-effective, environmentally friendly means of domestic solar panel cleaning.